Direct growth of doping controlled monolayer WSe2 by selenium-phosphorus substitution. Issue 24 (7th June 2018) - Kang, Won Tae; Lee, Il Min; Yun, Seok Joon; Song, Young Il; Kim, Kunnyun; Kim, Do-Hwan; Shin, Yong Seon; Lee, Kiyoung; Heo, Jinseong; Kim, Young-Min; Lee, Young Hee; Yu, Woo Jong
Abstract : The doping controlled growth of the transition metal dichalcogenide monolayer WSe2 was demonstrated by the replacement of selenium with phosphorus. Abstract : Although many studies have been carried out on the doping of transition metal dichalcogenides (TMDCs), introducing controllable amounts of dopants into a TMD lattice is still insufficient. Here we demonstrate doping controlled TMDC growth by the replacement of selenium with phosphorus during the synthesis of the monolayer WSe2 . The phosphorus doping density was precisely controlled by fine adjustment of the amount of P2 O5 dopant powder along the pre-annealing time. Raman spectroscopy, photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), and high-angle annular bright field scanning tunneling electron microscopy (HAADF STEM) provide evidence that P doping occurs within the WSe2 crystal with P occupying the substitutional Se sites. With regard to its electrical characteristics, the hole majority current of P-doped WSe2 is 100-times higher than that of the intrinsic WSe2 . The measured doping concentration ranged from ∼8.16 × 10 10 to ∼1.20 × 10 12 depending on the amount of P2 O5 dopant powder by pre-annealing.